Bandgap engineering in massive-massless graphene superlattices - García-Cervantes, H.; López-Becerra, A.; Rodríguez-González, R.; Rodríguez-Vargas, I. (Physica. B, Condensed matter, 2022)
Bandgap engineering in graphene has become a fervent subject of research due to its relevance in technological applications. In this work, we proposed massive-massless graphene superlattices (MMGSLs) to tune the angle-dependent transmission properties. We have considered breaking symmetry substrates to generate massive and massless regions. We report an angular dependence of the transmission gaps and minibands as a function of the angle of incidence of the Dirac electrons in MMGSLs. Our results show that the transmission gaps and minibands have a trigonometric angular dependence based on the secant in the entire transmission energy range. In addition, the transmission gaps and minibands are well-defined at normal incidence, in contrast to gated graphene superlattices. These findings indicate that MMGSLs could be a possibility for bandgap engineering in graphene.